Circumference-Based Predictions of Body Fat Revisited: Preliminary Results From a US Marine Corps Body Composition Survey - Potter, Adam W.; Tharion, William J.; Holden, Lucas D.; Pazmino, Angie; Looney, David P.; Friedl, Karl E. (Frontiers in Physiology, 2022)
Purpose: Body composition assessment methods are dependent on their underlying principles, and assumptions of each method may be affected by age and sex. This study compared an abdominal circumference-focused method of percent body fat estimation (AC %BF) to a criterion method of dual-energy x-ray absorptiometry (DXA), and a comparative assessment with bioelectrical impedance (BIA), in younger (≤30y) and older (>age 30y) physically fit (meeting/exceeding annual US Marine Corps fitness testing requirements) men and women. Methods: Fit healthy US Marines (430 men, 179 women; 18-57y) were assessed for body composition by DXA (iDXA, GE Lunar), anthropometry, and BIA (Quantum IV, RJL Systems). Results: Compared to DXA %BF, male AC %BF underestimated for both ≤30 and >30y age groups (bias, -2.6 ± 3.7 and -2.5 ± 3.7 %); while and female AC %BF overestimated for both ≤30 and >30y age groups (2.3 ± 4.3 and 1.3 ± 4.8 %). On an individual basis, lean men and women were overestimated and higher %BF individuals were underestimated. Predictions from BIA were more accurate and reflected less relationship to adiposity for each age and sex group (males: ≤30, 0.4 ± 3.2, >30y, -0.5 ± 3.5; females: ≤30, 1.4 ± 3.1, >30y, 0.0 ± 3.3). Total body water (hydration) and bone mineral content (BMC) as a proportion of fat-free mass (FFM) remained consistent across the age range; however, women had a higher proportion of %BMC/FFM than men. Older men and women (>age 30y) were larger and carried more fat but had similar FFM compared to younger men and women. Conclusion: The AC %BF provides a field expedient method for the US Marine Corps to classify individuals for obesity prevention, but does not provide research-grade quantitative body composition data.